(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
We present part of the research that rescues the performance of Maria Sophia Jobim Magno de Carvalho (1904-1968) as a movie costume designer. An artist specializing in clothing, Sophia designed the costumes for the p/w film Sinhá Moça (1953), an adaptation of the homonymous novel written by Maria Dezonne (1910-1998). So far, the sketches of Sinhá Moça have not been located in Sophia’s collection (deposited at the National Historical Museum - MHN), so we have prepared the colored sketches for the protagonist. We chose one of the 13 costumes to demonstrate our creative process from the image of period costumes in greyscale to the color graphic representation.